Barriers to mental health care utilization among internally displaced persons in the republic of Georgia: a rapid appraisal study - Adrianna Murphy; Ivdity Chikovani; Maia Uchaneishvili; Nino Makhashvili; Bayard Roberts (BMC, 2018)
Abstract Background There is a paucity of evidence on access to services for mental health and psychosocial support for conflict-affected populations in low- and middle-income countries. In the Republic of Georgia, rates of utilization of mental health services among internally displaced people with mental disorders are low. We set out to identify the health system barriers leading to this treatment gap. Methods We used rapid appraisal methods (collection and triangulation of multiple data sources) to investigate barriers to accessing mental health care services among adult IDPs in Georgia. Data collection included review of existing policy documents and other published data, as well as semi-structured interviews with 29 key informants including policy makers, NGO staff, health professionals and patients. Results The following factors emerged as important barriers affecting access to mental health care services among IDPs in Georgia: inadequate insurance coverage of mental disorders and poor identification and referral systems, underfunding, shortage of human resources, poor information systems, patient out-of-pocket payments and stigmatization. Conclusion While rapid appraisal methods cannot control for potential biases or achieve representativeness, triangulation supports internal validity and reliability of the data collected, allowing data to be used to inform health care interventions. The appropriateness and potential effectiveness of policy interventions such as insurance coverage of a wider range of mental disorders, integration of services for these at the primary health care level, and community-based approaches in this context should be explored.